2014
DOI: 10.1093/mp/ssu087
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Complexity in a Transcriptionally Centered Signaling Hub in Arabidopsis

Abstract: A subfamily of four Phytochrome (phy)-Interacting bHLH transcription Factors (PIFs) collectively promote skotomorphogenic development in dark-grown seedlings. This activity is reversed upon exposure to light, by photoactivated phy molecules that induce degradation of the PIFs, thereby triggering the transcriptional changes that drive a transition to photomorphogenesis. The PIFs function both redundantly and partially differentially at the morphogenic level in this process. To identify the direct targets of PIF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
236
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(258 citation statements)
references
References 87 publications
21
236
1
Order By: Relevance
“…Because previous studies have shown that PIFs positively regulated auxin biosynthesis in response to high temperature or shade (36)(37)(38), the degradation of PIFs should cause some of the decrease in auxin levels after light illumination in hypocotyls. The differential regulation of target genes by PIFs may be achieved by their cofactors, and this speculation is supported by previous ChIP-seq and RNA-seq data, which showed that PIFs may both positively and negatively regulate their target genes (16)(17)(18). Based on our transcriptomic analysis, thousands of genes are differentially expressed in cotyledons and hypocotyls (subgroup 7 in Dataset S6), and some may work as PIF cofactors.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Because previous studies have shown that PIFs positively regulated auxin biosynthesis in response to high temperature or shade (36)(37)(38), the degradation of PIFs should cause some of the decrease in auxin levels after light illumination in hypocotyls. The differential regulation of target genes by PIFs may be achieved by their cofactors, and this speculation is supported by previous ChIP-seq and RNA-seq data, which showed that PIFs may both positively and negatively regulate their target genes (16)(17)(18). Based on our transcriptomic analysis, thousands of genes are differentially expressed in cotyledons and hypocotyls (subgroup 7 in Dataset S6), and some may work as PIF cofactors.…”
Section: Discussionsupporting
confidence: 80%
“…In Arabidopsis, single or multiple loss-of-function mutants of PIF genes display short hypocotyls in red light and in the dark, indicating that PIFs are repressors of photomorphogenesis (13). Chromatin immunoprecipitation (ChIP)-chip and ChIP-Seq studies have shown that PIFs regulate thousands of downstream genes (14)(15)(16)(17)(18). These genes are released from the control of the PIFs upon illumination because light suppresses both the amounts and the activities of the PIFs in various ways (19).…”
mentioning
confidence: 99%
“…We confirmed the importance of PIFs beyond shadeinduced auxin production in cotyledons by comparing the auxin responsiveness of yuc2 yuc5 yuc8 yuc9 and pif4 pif5 pif7 mutants (Supplemental Figure 4F) (Nozue et al, 2011;Hornitschek et al, 2012;Hersch et al, 2014). Consistent with the additive function of PIF4 and PIF5 during shade avoidance (Lorrain et al, 2008;Hornitschek et al, 2012;Pfeiffer et al, 2014), both bound to a highly overlapping set of shade-induced genes (Figure 3). The rapid and strong overrepresentation of auxin-regulated genes among our shade-regulated gene list (Figures 2 and 4) prompted us to determine whether many of these genes are also bound by ARF transcription factors (Guilfoyle, 2015).…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, given that many PIF target genes are themselves transcriptional regulators (Hornitschek et al, 2012;Oh et al, 2012;Pfeiffer et al, 2014), this finding suggests the involvement of other transcription factors later in the response. PIFs are known to share many target genes; for example, PIF4, PIF5, and PIF7 bind to the YUC8 promoter (Hornitschek et al, 2012;Li et al, 2012;Pfeiffer et al, 2014). We tested the degree of PIF binding overlap by reanalyzing genome-wide PIF4 ChIP (chromatin immunoprecipitation) data in etiolated seedlings .…”
Section: Pif Transcription Factors Directly Regulate Many Early Shadementioning
confidence: 93%
“…RNA was isolated from 3-d-old dark-grown wild-type Col-0, pif1, pifQ, and hec1 hec2 seedlings. RT-qPCR was performed for PIL1, PIL2, HFR1, FHL, SDR, XRT7, and AtHB-2, which are the direct targets of PIFs as previously shown (Zhang et al, 2013;Pfeiffer et al, 2014). Results show that the expression of all those PIF target genes is stimulated in the hec1 hec2 mutant compared with the wild type in the dark ( Figure 5B).…”
Section: Hec Proteins Regulate the Indirect And Direct Target Genes Osupporting
confidence: 60%